2011
DOI: 10.1007/s00221-011-2874-x
|View full text |Cite
|
Sign up to set email alerts
|

The stability of rhythmic movement coordination depends on relative speed: the Bingham model supported

Abstract: Following many studies showing that the coupling in bimanual coordination can be perceptual, Bingham (Ecol Psychol in 16:45-53, 2001; 2004a, b) proposed a dynamical model of such movements. The model contains three key hypotheses: (1) Being able to produce stable coordinative movements is a function of the ability to perceive relative phase, (2) the information to perceive relative phase is relative direction of motion, and (3) the ability to resolve this information is conditioned by relative speed. The first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
71
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(73 citation statements)
references
References 35 publications
2
71
0
Order By: Relevance
“…Kelso et al 1986;Kelso et al 1987). Simulations of the unimanual model showed that 180° movements only remained stable up to ≈1.5 Hz, again matching the empirical data (Snapp-Childs et al 2011). Other than this, the unimanual model produces all the same coordination phenomena as the bimanual model.…”
Section: Introductionsupporting
confidence: 75%
See 3 more Smart Citations
“…Kelso et al 1986;Kelso et al 1987). Simulations of the unimanual model showed that 180° movements only remained stable up to ≈1.5 Hz, again matching the empirical data (Snapp-Childs et al 2011). Other than this, the unimanual model produces all the same coordination phenomena as the bimanual model.…”
Section: Introductionsupporting
confidence: 75%
“…Finally, Snapp-Childs et al (2011) showed in model simulations and confirmed with data that performance in the uni-manual tasks is inherently less stable than in the bi-manual tasks because the coupling is uni-directional instead of bi-directional. Thus, we must expect the level of improvement in performance, after equivalent amounts of training, to be less in the unimanual task than in the bi-manual task.…”
Section: The Current Experimentssupporting
confidence: 61%
See 2 more Smart Citations
“…Indeed, they have shown that the information that can be used to control rhythmic visuomotor coordination is the relative direction between the observed and produced movements and that the detection of this information depends on the relative speed between these two movements that acts as noise (Bingham, 2004a(Bingham, , 2004bSnapp-Childs et al, 2011;Wilson et al, 2005a;Wilson, Collins, & Bingham, 2005b). When performing an in-phase or antiphase coordination, the relative direction does not change (always the same and always different at 0°and 180°, respectively), but antiphase coordination is less stable because the relative speed ranges from zero to maximally different, which degrades the detection of the relative direction information.…”
Section: Discussionmentioning
confidence: 99%